2012
DOI: 10.33549/physiolres.932396
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lifestyle-Related Risk Factors on Cardiac Response to Ischemia and Possibilities to Restore Impaired Ischemic Tolerance

Abstract: Risk factors (RF) of cardiovascular diseases associated with modern lifestyle, such as stress, chronically increased blood pressure, hyperglycemia and dyslipidemia have a negative impact on the heart exposed to ischemia: their may facilitate its lethal injury (myocardial infarction) and occurrence of sudden death due to ventricular arrhythmias. On the other hand, some stressful stimuli related to RF including reactive oxygen species, transient episodes of ischemia (hypoxia), high glucose and other may play a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…However, the physiological and molecular mechanisms and related signalling pathways of IAP in intestinal inflammation in vitro have not been reported. In the present study, PI3kinase comprises a P110 catalytic subunit and a P85 regulatory subunit, which can be activated when P85 is activated (76); then, PI3K transmits signals to Akt, which induces a series of inflammatory responses. CXCL9 was downregulated in the IAP + LPS group upon binding to CXCR3 and CXCR3, resulting in Src phosphorylation and increasing the Src kinase activity; consequently, phosphatidylinositol 3 kinase (PI3K) activity increased, leading to an increase in Akt activity (37).…”
Section: Discussionmentioning
confidence: 90%
“…However, the physiological and molecular mechanisms and related signalling pathways of IAP in intestinal inflammation in vitro have not been reported. In the present study, PI3kinase comprises a P110 catalytic subunit and a P85 regulatory subunit, which can be activated when P85 is activated (76); then, PI3K transmits signals to Akt, which induces a series of inflammatory responses. CXCL9 was downregulated in the IAP + LPS group upon binding to CXCR3 and CXCR3, resulting in Src phosphorylation and increasing the Src kinase activity; consequently, phosphatidylinositol 3 kinase (PI3K) activity increased, leading to an increase in Akt activity (37).…”
Section: Discussionmentioning
confidence: 90%
“…The apoptosis of cardiomyocytes often occurs throughout the process of heart disease, and improvement of cardiac function largely relies on the surviving cardiomyocytes ( 21 , 22 ). It has been demonstrated that oxidative stress is the main cause of hypoxic and ischemic heart diseases ( 23 , 24 ). Under pathological conditions, the balance between the production and clearance of ROS is disrupted.…”
Section: Discussionmentioning
confidence: 99%